Outcomes in juvenile onset lupus: single center cohort from a developing country. (October 2018) - Aggarwal, A; Phatak, S; Srivastava, P; Lawrence, A; Agarwal, V; Misra, R
Introduction: About 10–20% of systemic lupus erythematosus (SLE) patients have onset in childhood and have more severe organ involvement. Survival of juvenile SLE patients is improving worldwide. Long-term data of childhood onset SLE from developing countries is scarce. Methods: Clinical and laboratory data at initial presentation and follow-up visits were retrieved from clinic files, hospital information system and personal interviews. Treatment received, complications, flares, outcomes and death were recorded. Survival was calculated using Kaplan–Meier survival curves and regression analysis was done for predictors of mortality. Results: Children with SLE ( n  = 273, 250 girls) had a median age at onset of 14 years and duration of illness prior to diagnosis at our hospital of 1 year. Fever and arthritis were the most common presenting manifestations. Renal disease was seen in 60.5% and central nervous system (CNS) disease in 29%. The median follow-up period in 248 patients was 3.5 years. Fourteen children died, and 10 of these had active disease at the time of death. The mean actuarial survival was 24.5 years and survival rates at 1, 5 and 10 years were 97.9%, 95% and 89% respectively. Fever, CNS disease, anti-dsDNA levels and serious infections predicted death on univariate and multivariate analysis. Infections were seen in 72 children (26.3%), and 38 of these infections were serious. One-third of the patients had damage on the last follow-up. Flares were seen in 120 children, the majority being major flares. Conclusion: Outcomes of pediatric SLE in North Indian children are similar to those seen in developed countries. Infections pose a major challenge in these patients.